2021
DOI: 10.1101/2021.10.25.465799
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nelfinavir induces cytotoxicity towards high-grade serous ovarian cancer cells, involving induction of the unfolded protein response, modulation of protein synthesis, DNA damage, lysosomal impairment, and potentiation of toxicity caused by proteasome inhibition

Abstract: High-grade serous ovarian cancer (HGSOC) is a significant cause of mortality among women worldwide. Traditional treatment consists of platinum-based therapy; however, rapid development of platinum resistance contributes to lower life expectancy, warranting newer therapies to supplement the current platinum-based protocol. Repurposing market-available drugs as cancer therapeutics is a cost- and time-effective way to avail new therapies to drug-resistant patients. The anti-HIV agent nelfinavir (NFV) has shown pr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 95 publications
0
5
0
Order By: Relevance
“…We used a pair of cell lines termed PEO1 and PEO4 which have different sensitivities to platinum. For instance, we recently demonstrated that PEO4 cells are about ten times less sensitive to cisplatin than their PEO1 siblings obtained from the same patient earlier during disease evolution [15]. Despite the large difference in platinum sensitivity among the two cell lines (Figures 1A and 1B), both cellular types responded to increased concentrations of auranofin with similar impairment in wellbeing as denoted by the similar decrease in their vitality (Figures 2C and 2D).…”
Section: Auranofin Reduces the Vitality Of Hgsoc Cells Regardless Of ...mentioning
confidence: 78%
See 3 more Smart Citations
“…We used a pair of cell lines termed PEO1 and PEO4 which have different sensitivities to platinum. For instance, we recently demonstrated that PEO4 cells are about ten times less sensitive to cisplatin than their PEO1 siblings obtained from the same patient earlier during disease evolution [15]. Despite the large difference in platinum sensitivity among the two cell lines (Figures 1A and 1B), both cellular types responded to increased concentrations of auranofin with similar impairment in wellbeing as denoted by the similar decrease in their vitality (Figures 2C and 2D).…”
Section: Auranofin Reduces the Vitality Of Hgsoc Cells Regardless Of ...mentioning
confidence: 78%
“…PEO1 cells are epithelial ovarian cancer cells isolated from a patient after its first relapse 22 months following treatment with cisplatin, 5-fluorouracil, and chlorambucil, while the patient was still sensitive to platinum-based chemotherapy; PEO4 cells were subsequently isolated from the same patient after the second relapse in which the patient was no longer sensitive to the chemotherapy. These cell lines were histologically characterized in 1988 and sequenced in 2010 [29,30], whereas we authenticated them in 2020 based on their autosomal short-tandem repeats [15]. The cells were cultured in RPMI 1640 media (Mediatech, Manassas, VA, USA) supplemented with 5% fetal bovine serum (FBS) (Atlanta Biologicals, Lawrenceville, GA, USA), 5% bovine serum (Life Technologies, Auckland, New Zealand), 0.01 mg/mL of human insulin (Roche, Indianapolis, IN, USA), 10 mM HEPES (Corning, Corning, NY, USA), 100 IU penicillin (Mediatech), 100 μg/mL streptomycin (Mediatech), 2 mM L-Alanyl-L-Glutamine 6 (Glutagro TM , Corning) and 1 mM sodium pyruvate (Corning).…”
Section: Reagents and Cell Linesmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, there are many related reports on the role of drug repositioning in ovarian cancer treatment ( 4 , 5 ), such as lipid-lowering drug statins ( 6 ), glucose-lowering drug metformin ( 7 ), antiarrhythmic drug amiodarone ( 8 ), neuroprotective drugs ( 9 ), ACEI for hypertension ( 10 ), disulfiram for chronic alcoholism anti-inflammatory ( 11 , 12 ), anti-bacterial ( 13 , 14 ), anti-viral ( 15 ), and anti-parasitic drugs ( 16 , 17 ) as well as calcium-channel blockers ( 18 ), have all shown different anti-ovarian cancer effects. However, there were huge differences in the specific results.…”
Section: Introductionmentioning
confidence: 99%